2010
DOI: 10.4081/rt.2010.e36
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of c-kit in small venous malformations of blue rubber bleb nevus syndrome

Abstract: The blue rubber bleb nevus syndrome (BRBNS, syn. bean syndrome) is a rare disease characterized by multiple cutaneous and gastrointestinal venous malformations associated with severe bleeding. However, the underlying molecular mechanisms are unknown and no targeted therapeutic approach exists to date. Here we report the case of a 19-year-old male patient with severe BRBNS in whom we analyzed the expression of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…[ 5 ] The etiology and pathogenesis of this syndrome remained unknown; locus on chromosome 9P, elevated c-kit expression may be involved on molecular and genetic level. [ 6 ] Although an autosomal dominant inheritance had been described in several familial cases, the majority of the cases appeared to be sporadic [ 7 ] ; no family history of BRBNS was found in our group also. The venous malformations were primarily located on the skin and GI tract.…”
Section: Discussionmentioning
confidence: 50%
“…[ 5 ] The etiology and pathogenesis of this syndrome remained unknown; locus on chromosome 9P, elevated c-kit expression may be involved on molecular and genetic level. [ 6 ] Although an autosomal dominant inheritance had been described in several familial cases, the majority of the cases appeared to be sporadic [ 7 ] ; no family history of BRBNS was found in our group also. The venous malformations were primarily located on the skin and GI tract.…”
Section: Discussionmentioning
confidence: 50%
“…Elevated expression of c-KIT has also been found in small venous malformations in the blue rubber bleb nevus syndrome. 12 Mutations in KIT occur in germline or somatic configuration. Germline mutations of exons 11, 13, and 17 of the KIT gene are frequently reported in familial and multiple GIST, 13 familial mastocytosis, 14 and aggressive fibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…While autosomal dominant inheritance has been reported, most cases of BRBNS occur spontaneously, as in the present case. The pathogenesis of BRBNS remains unclear; however, it has been suggested that a locus on chromosome 9P responsible for venous malformation and elevated c-kit expression may be involved [ 8 , 9 ]. Although BRBNS is an uncommon syndrome, physical examination of the patient, GI imaging tests, and circumstantial questioning can help make a diagnosis.…”
Section: Discussionmentioning
confidence: 99%